(3NhGJe GdMce hMd GdQehR hcTa GdcfhRs - (3GdehSJGQj, Ke GdScJhGQj, , YdGA GdOjf, Ydj OOg, TjN GdJQHI, Ydj Hf eUWai, J (B1007 (3g`s ((3eOjfI GdfjTs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdYdj GdCYde deG CJeeJ cJGHj GdChGFd hGdChGNQ GSNQJ Gddg Cf CLeY QSGdI aQjOI hSejJgG NhGJe GdMce hMd GdQehR hcTa GdcfhR s
(3BNQgG (B:s
(3Yf CfS QVj Gddg Yfg bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde dG Jbhe GdSGYI MJi dG ojbGd aj GdCQV Gddg Gddg s
(3aj Chdg agQS (B- (3hCOYjI hJhGQjN HGdJQcjI (B- (3hfbhd (B- (3fSNI ePgHI heRNQaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/287s
(3eYLe GdeDdajf (B2/532s
(3NdGUI GdCKQ (B3s
(3gOjI GdYGQajf (B1/750s
Keywords: (3GdeYGQa GdYGeIs